2013
DOI: 10.1111/ahe.12023
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Gastrin, Somatostatin and Glucagon Immunoreactive (IR) Cells in Ostrich Stomach During the Pre- and Post-hatching Period

Abstract: Peptides of the gastrointestinal tract play a significant role in the digestive processes and the development of the body; therefore, it is important to have an understanding of location and distribution of gastrin, somatostatin and glucagon immunoreactive (IR) cells in the stomach mucosa of growing birds. For this purpose, 6 embryos and 37 chicks from an ostrich farm in Latvia were used. Tissue samples were collected from the proventriculus - superficial and deep glandular region and from the ventriculus - si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…I-cells, L-cells) have been described and well characterised along the mammalian gastrointestinal tract (Gunawardene et al, 2011;Latorre et al, 2016). In birds, several types of EECs (homologous to those in mammals) have been identified and several studies describe their distribution and morphology in the gastrointestinal tract of different species [chick, Gallus gallus domesticus (Aksoy and Cinar, 2009;Arcamone et al, 2014;Hiramatsu, 2020;Neglia et al, 2005;Reid and Dunn, 2018;Salvi et al, 1996); ostrich, Struthio camelus (Duritis et al, 2013); rufous-collared sparrow, Zonotrichia capensis subtorquata (Mendes et al, 2009)]. Compared with mammals and birds, the knowledge of EEC types in other vertebrates is scarce.…”
Section: Endocrine Connection From the Gut To The Brainmentioning
confidence: 99%
“…I-cells, L-cells) have been described and well characterised along the mammalian gastrointestinal tract (Gunawardene et al, 2011;Latorre et al, 2016). In birds, several types of EECs (homologous to those in mammals) have been identified and several studies describe their distribution and morphology in the gastrointestinal tract of different species [chick, Gallus gallus domesticus (Aksoy and Cinar, 2009;Arcamone et al, 2014;Hiramatsu, 2020;Neglia et al, 2005;Reid and Dunn, 2018;Salvi et al, 1996); ostrich, Struthio camelus (Duritis et al, 2013); rufous-collared sparrow, Zonotrichia capensis subtorquata (Mendes et al, 2009)]. Compared with mammals and birds, the knowledge of EEC types in other vertebrates is scarce.…”
Section: Endocrine Connection From the Gut To The Brainmentioning
confidence: 99%
“…Pirone et al (2011) determined the distribution of the gastric inhibitory polypeptide (GIP), a mammalian incretin hormone, and the gastrin-releasing peptide (GRP), which has regulatory functions in the central nervous system and gastrointestinal tract of mammals. Distribution of various endocrine cells has also been investigated in the gastrointestinal tract of birds such as Passeriformes (Mendes et al, 2009), pheasant (Pirone et al, 2012), and ostrich (Duritis et al, 2013).…”
Section: Endocrine Cells Of the Avian Gastrointestinal Tractmentioning
confidence: 99%
“…So for many years, scholars have studied the morphology of the proventriculus in different animals (Fang, 2005;He, 2002;Sun, 2012;Shen, 2000;Kadhim, 2011;Li, 2006;Zhang et al, 2016), the researches showed that the morphological characteristics of different animals were different. While on the ostriches, studies mainly focused on its gross anatomy and gland cells (Xu, 2005;Chen, 2013;Duritis et al, 2013;Streicher, 1985). So far there has been seldom systematic report on the morphology of the proventriculus of African ostrich, so the present study was planned.…”
Section: Introductionmentioning
confidence: 99%